EFFECTIVENESS OF THE DPRD RECESS PROGRAM IN ABSORBING PUBLIC ASPIRATIONS - Suryaningsih; Muhammad Husein Maruapey; Deny Hernawan (Administratie: Jurnal Administrasi Publik, 2025)
The recess activities of members of the Regional People's Representative Council (DPRD) are an official and strategic agenda designed to bridge communication between the legislative branch and the public. The goal is to ensure that public aspirations, needs, and issues are effectively absorbed and become the basis for policy. This study aims to analyze the effectiveness of recess in absorbing aspirations by focusing on three key indicators: the level of public participation, the alignment of aspirations with real needs, and the realization of follow-up on the aspirations expressed. This study uses a descriptive qualitative method to obtain an in-depth and comprehensive picture. Data collection was conducted through in-depth interviews and field observations. The collected data were analyzed thematically to identify patterns, key issues, and relevant conclusions. Research informants were selected purposively to represent a variety of perspectives, including council members who directly implemented the recess, council personal assistants who documented and facilitated the process, community leaders who served as representatives and liaisons at the community level, and the general public who directly participated in the recess activities. The research results show that recess does provide ample space for public participation, particularly in conveying aspirations regarding social assistance and infrastructure development. However, its effectiveness still faces significant obstacles. The main obstacles include unequal regional distribution, where not all areas receive equal attention; limited socialization of activities, leaving many people unaware of the recess schedule; and often slow or unclear follow-up. The novelty of this research lies in its analysis, which not only identifies the problems but also links the effectiveness of recess to three key interconnected factors: public participation, multi-channel communication, and a monitoring system. This research emphasizes that the success of recess depends not only on face-to-face meetings but also on how aspirations are systematically followed up. Based on these findings, the research recommends the need for data-driven evaluation to ensure a more equitable and transparent process and to improve equity in the distribution of benefits resulting from community aspirations.